A structured literature review and international consensus validation of FORTA labels of oral anticoagulants for long-term treatment of atrial fibrillation in older patients (OAC-FORTA 2019) - Pazan, Farhad; Collins, Ronan; Gil, Victor M.; Hanon, Olivier; Hardt, Roland; Hoffmeister, Martin; Monteiro, Pedro; Quinn, Terence J.; Ropers, Dieter; Sergi, Giuseppe; Verheugt, Freek W. A.; Wehling, Martin (Drugs & aging, 2020)
Evidence regarding safety and efficacy of oral anticoagulants for the treatment of atrial fibrillation (AFib) in older adults has been assessed regarding the age appropriateness of oral anticoagulants (OAC) according to the FORTA (Fit fOR The Aged) classification (OAC-FORTA). Three years after its first version (OAC-FORTA 2016), an update was initiated to create OAC-FORTA 2019.